Study of The Interaction Carbondioxide Gas with Hydroxyapatite Using Density Functional Theory - Atiek Rostika Noviyanti; Azhari Yusuf; Yeni Wahyuni Hartati; Budi Adiperdana (Jurnal Keramik dan Gelas Indonesia, 2021)
Hydroxyapatite (HA) is a phosphate mineral with Ca10(PO4)6(OH)2 chemical formula. The hydroxyl group in HA allows ion to exchange, so this material may be applied as a CO2 gas sensor. The interaction between HA with CO2 gas is difficult to observe directly, and ab initio modeling is necessarily to investigate the interactions between HA with CO2 gas. In this study, a simulation was conducted using the density functional theory method to determine the interaction between CO2 gas on the surface of HA. The simulation results indicate that a large HA surface is required for optimal CO2 gas adsorption. Pore diameter size needs to be larger than 2.5 Å to prevent binding on two sides of the surface pores.